Day-of-the-week effect on stock returns / Noor Ain Shafiqah Ahmad Saharuddin - Ahmad Saharuddin, Noor Ain Shafiqah (2017)
This study examines the day-of-the-week effect on stock returns of FTSE Bursa Malaysia Kuala Lumpur Composite Index (FBM KLCI) from 05 March 2007 until 1 July 2016 using Ordinary Latest Square (OLS) Method. The findings suggest that there exist the 'Monday effect' and significantly different across the five trading days. This finding is also similitary in other periods. The study using of several diagnostic test such as normality of errors, autocorrelation and heteroskedasticity in order to check for model adequacy. Last but not least, this study may be useful to the investor in order to formulate their strategies of trades timing.